Socialization and Legal Counseling on Cyber Crime and Personal Data Protection In the Digital Age (Sosialisasi dan Penyuluhan Hukum Kejahatan Dunia Maya dan Perlindungan Data Pribadi di Era Digital) - Sinaga, M. Hary Angga Pratama; Rizky, M. Chaerul; Sari, Maya Macia; Daulay, Soni Rohima (UKInstitute, 2025)
The advancement of digital technology has had a positive and negative impact on society. On the one hand, easy access to information and communication increases productivity. But on the other hand, cybercrimes such as data theft, fraud, and the spread of illegal content are increasing. This community service activity aims to provide a comprehensive understanding to the public about cybercrime, personal data protection, and strategies for preventing and overcoming cybercrime. Through the method of socialization and counseling, the service team delivered material on the types of cyber crimes, the impact caused, and legal remedies that could be taken. In addition, participants were also equipped with knowledge about the importance of personal data protection and how to secure digital information. This activity is expected to increase public awareness and vigilance in using digital technology safely and responsibly, as well as minimize the risk of becoming a victim of cybercrime.Abstrak: Kemajuan teknologi digital telah memberikan dampak positif dan negatif bagi masyarakat. Di satu sisi, kemudahan akses informasi dan komunikasi meningkatkan produktivitas. Namun di sisi lain, kejahatan dunia maya seperti pencurian data, penipuan, dan penyebaran konten ilegal semakin marak. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk memberikan pemahaman yang komprehensif kepada masyarakat tentang kejahatan dunia maya, perlindungan data pribadi, serta strategi pencegahan dan penanggulangan kejahatan dunia maya. Melalui metode sosialisasi dan penyuluhan, tim pengabdian menyampaikan materi tentang jenis-jenis kejahatan dunia maya, dampak yang ditimbulkan, serta upaya hukum yang dapat ditempuh. Selain itu, peserta juga dibekali dengan pengetahuan tentang pentingnya perlindungan data pribadi dan cara mengamankan informasi digital. Kegiatan ini diharapkan dapat meningkatkan kesadaran dan kewaspadaan masyarakat dalam menggunakan teknologi digital secara aman dan bertanggung jawab, serta meminimalisir risiko menjadi korban kejahatan dunia maya.